A Systematic Review and Meta-Analysis of Nutritional Supplementation in Chronic Lower Extremity Wounds - Ye J. (2017)
© The Author(s) 2016. A systematic review and meta-analyses of nutritional supplementation to treat chronic lower extremity wounds was done in order to test the premise that impaired nutrition is implicated in healing. The databases of Ovid MEDLINE, Ovid EMBASE, Cochrane Library, and EBSCO CINAHL (1972-October 2014) were searched systematically. Only randomized controlled trials in adults with chronic lower extremity wounds were included. Both topical and systemic routes of supplementing nutrition were considered. The primary outcome was wound healing. Study characteristics, outcomes, and risk of bias were extracted by trained researchers and confirmed by the principal investigator. Twenty-three of 278 (8.3%) retrieved articles met the inclusion criteria and were selected. Most of the studies were of unclear or low risk. Overall, nutritional supplementation was favorable (risk ratio [RR] = 1.44, 95% confidence interval [CI] = 1.25-1.66). The systemic route was marginally better than the topical one (RR = 1.51, 95% CI = 1.36-1.67; RR = 1.14, 95% CI = 0.96-1.36, respectively). For venous ulcers, the data showed nutritional supplementation to be significantly beneficial compared to placebo (RR = 1.44, 95% CI = 1.31-1.59). Similar data were found for diabetic foot and sickle cell ulcers (RR = 1.17, 95% CI = 0.93-1.47; RR = 1.56, 95% CI = 0.94-2.60, respectively). These data permit the inferences that nutritional supplementation in the populations studied showed significant benefits in the healing of venous ulcers and tendency (nonsignificant trends) in the healing of diabetic and sickle cell ulcers.